A Review on Favourable Maximum Power Point Tracking Systems in Solar Energy Application - Awang Jusoh; Tole Sutikno; Tan Kar Guan; Saad Mekhilef (Universitas Ahmad Dahlan, 2014)
This paper reviews different types of maximum power point tracking (MPPT) techniques for solar photovoltaic (PV) application. Since the PV output power is known affected by sun radiation and temperature, it is necessary to search for an effective method for extracting maximum amount of power from PV cell/modules. In this study, a total of seven control algorithms were selected, comprising the most popular methods among the established techniques. A comparison in terms of convergence speed, complexity, as well as the basic concept of each method had been carried out for future reference. Based on the accessible simulation results, modified Perturb and Observe (P&O) method had shown its effectiveness for obtaining actual maximum power point while solving major drawbacks of the conventional P&O. This paper also discusses typical solar MPPT system, including the pros and cons of each part of the system.